Irritable bowel syndrome among nurses working in King Abdulaziz University Hospital, Jeddah, Saudi Arabia. Issue 1 (1st January 2016) - Ibrahim, Nahla Khamis; Al-Bloushy, Randa Ibrahim; Sait, Salma Hani; Al-Azhary, Hatoon Wahid; Bar, Nusaybah Hussain Al; Mirdad, Ghazal A.
Abstract : Background: Irritable bowel syndrome (IBS) is a highly prevalent gastrointestinal disorder that can cause disability and economic burden. Nurses are a vital part of the medical team and their well-being is an important issue. Yet, few studies have been done concerning IBS among nurses. Objectives: To determine the prevalence, severity, and predictors of IBS among nurses working at King Abdulaziz University Hospital, Jeddah, Saudi Arabia. Materials and methods: A cross-sectional study was conducted among 229 nurses who fulfilled the eligibility criteria. They were selected by stratified random sampling during 2014–2015. A validated, confidential, self-administered data collection sheet was used for collection of personal and sociodemographic data. Rome III Criteria, IBS Severity Scoring System (IBS-SSS), Hospital Anxiety and Depression Scale (HADS), and Pittsburgh Sleep Quality Index (PSQI) were included. Both descriptive and inferential statistics were done. A multiple logistic regression analysis was done to determine the predictors of IBS. Results: The prevalence of IBS among nurses was 14.4%, and IBS-Mixed type was the commonest variety (54.5%). Positive family history of IBS, working in outpatient clinics, having day shift, poor sleep quality, and high anxiety and depression scale scores were significantly associated with IBS. After controlling for confounding factors in regression analysis, the predictors of IBS were food hypersensitivity (aOR=4.52; 95% CI: 1.80−11.33), morbid anxiety (aOR=4.34; 95% CI: 1.49–12.67), and positive family history of IBS (aOR=3.38; 95% CI: 1.12–13.23). Conclusion: The prevalence of IBS was 14.4%. Food hypersensitivity, morbid anxiety, and family history were the predictors of IBS. Screening and management of IBS, food hypersensitivity, and psychological problems among nurses are recommended.